Biomaterial aided differentiation and maturation of induced pluripotent stem cells. Issue 6 (22nd November 2018) - Velmurugan, Bharath Kumar; Bharathi Priya, Lohanathan; Poornima, Paramasivan; Lee, Li‐Jen; Baskaran, Rathinasamy
Abstract: Engineering/reprogramming differentiated adult somatic cells to gain the ability to differentiate into any type of cell lineage are called as induced pluripotent stem cells (iPSCs). Offering unlimited self‐renewal and differentiation potential, these iPSC are aspired to meet the growing demands in the field of regenerative medicine, tissue engineering, disease modeling, nanotechnology, and drug discovery. Biomaterial fabrication with the rapid evolution of technology increased their versatility and utility in regenerative medicine and tissue engineering, revolutionizing the stem cell biology research with the property to guide the process of proliferation, differentiation, and morphogenesis. Combining traditional culture platforms of iPSC with biomaterials aids to overcome the limitations associated with derivation, proliferation, and maturation, thereby could improve the clinical translation of iPSC. The present review discusses in brief about the reprogramming techniques for the derivation iPSC and details on several biomaterial guided differentiation of iPSC to different cell types with specific relevance to tissue engineering/regenerative medicine. Abstract : Recent technological advancements in biomaterial scaffolds aids to improve the differentiation of induced pluripotent stem cells (iPSCs) with desired properties. Here, we discuss in detail with examples that different fabrication techniques incorporates physical and topographical or biochemical cues in the biomaterial scaffold which guides in the differentiation of iPSCs to a specific functional cell phenotype.